2016
DOI: 10.1111/ffe.12516
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of very high cycle fatigue properties in an AA7075 friction stir welded joint by ultrasonic peening treatment

Abstract: The present paper aims to investigate the effect of ultrasonic peening treatment on the very high cycle fatigue resistance of an AA7075 friction stir welded joint. Microscopy observation, microhardness and X‐ray diffraction measurements were carried out to characterize the treated surface of peened specimens. Fatigue crack initiation sites were investigated through scanning electron microscope, and the role of enhanced surface on fatigue resistance was analyzed. The results indicate that a sensible fatigue str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The reason is that fatigue crack mostly initiates from free surfaces of cyclically loaded metals. To avoid these impacts, a number of surface hardening technologies such as carburizing, nitriding, and shot peening are widely used to improve the fatigue resistance of structural materials . However, with the concept of very high cycle fatigue (VHCF) being put forward, studies show that surface harden sometimes cannot improve the fatigue properties of structural materials .…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that fatigue crack mostly initiates from free surfaces of cyclically loaded metals. To avoid these impacts, a number of surface hardening technologies such as carburizing, nitriding, and shot peening are widely used to improve the fatigue resistance of structural materials . However, with the concept of very high cycle fatigue (VHCF) being put forward, studies show that surface harden sometimes cannot improve the fatigue properties of structural materials .…”
Section: Introductionmentioning
confidence: 99%
“…It revealed that the fatigue crack originated at the advancing side due to the effects of microstructural heterogeneity. Our previous work [12,13] also found that fatigue crack initiation sites were localized at the thermomechanically affected zone on the advancing side below 10 8 cycles. Nevertheless, the failure was prone to occur at the nugget zone in the VHCF regime.…”
Section: Introductionmentioning
confidence: 81%
“…Recently, the occurrence of very high cycle fatigue (VHCF), which is associated with unexpected failures in the life regime beyond 10 7 cycles under the applied stresses below the conventional fatigue limit, means that the traditional criteria for fatigue assessment evolved from infinite life to damage tolerance are sometimes not appropriate. Moreover, a number of fundamental VHCF problems such as duplex or stepwise S‐N curve characteristics, competing failure mechanisms, life prediction approach, etc., are not yet well understood . Therefore, in order to keep the long‐term safety of mechanical structure or components, the VHCF mechanisms of structural materials and the relevant fatigue assessment approach still need to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…For alloy steels, the interior failure is mainly caused from the interior nonmetallic inclusions or inhomogeneous microstructures . Generally, a fisheye‐shaped crack occurs on the fracture surface, in which a peculiar area, named “fine granular area (FGA)” by coauthor Sakai, sometimes can be observed in the vicinity of crack nucleus, but sometimes it does not occur even in the life regime beyond 10 8 cycles . Some ideas or models such as “Polygonization and debonding,” “Depressive decohesion of spherical carbide,” “Continuous grain refinement,” “Numerous cyclic pressing,” “Hydrogen embrittlement‐assisted cracking,” “Repeating contact of crack surfaces,” and “Stage I‐like crystallographic crack propagation” have been proposed to explain the formation mechanism of the FGA from the various viewpoints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation